Serum microRNAs associated with concussion in football players - Wyczechowska, Dorota; Harch, Paul G.; Mullenix, Shelly; Fannin, Erin S.; Chiappinelli, Brenda B.; Jeansonne, Duane; Lassak, Adam; Bazan, Nicolas G.; Peruzzi, Francesca (Frontiers in Neurology, 2023)
Mild Traumatic Brain Injury (mild TBI)/concussion is a common sports injury, especially common in football players. Repeated concussions are thought to lead to long-term brain damage including chronic traumatic encephalopathy (CTE). With the worldwide growing interest in studying sport-related concussion the search for biomarkers for early diagnosis and progression of neuronal injury has also became priority. MicroRNAs are short, non-coding RNAs that regulate gene expression post-transcriptionally. Due to their high stability in biological fluids, microRNAs can serve as biomarkers in a variety of diseases including pathologies of the nervous system. In this exploratory study, we have evaluated changes in the expression of selected serum miRNAs in collegiate football players obtained during a full practice and game season. We found a miRNA signature that can distinguish with good specificity and sensitivity players with concussions from non-concussed players. Furthermore, we found miRNAs associated with the acute phase (let-7c-5p, miR-16-5p, miR-181c-5p, miR-146a-5p, miR-154-5p, miR-431-5p, miR-151a-5p, miR-181d-5p, miR-487b-3p, miR-377-3p, miR-17-5p, miR-22-3p, and miR-126-5p) and those whose changes persist up to 4 months after concussion (miR-17-5p and miR-22-3p).